RELATIONSHIP OF MOTHER'S PREGNANCY DISTANCE AND HISTORY OF LOW BIRTH WEIGHT WITH LOW BIRTH WEIGHT IN BANGIL HOSPITAL, PASURUAN REGENCY - Kartika, Dewi; Riski Candra Kharisma; Meilly Dwidasa Ekawati (Jurnal Medicare, 2022)
The infant mortality rate in Indonesia increased in 2012 from 19% per 1,000 live births to 22.23% per 1,000 live births (SUPAS, 2015). The infant mortality rate in East Java province in 2013 was 27.23% per 1,000 live births (East Java Province Health Profile, 2014). Meanwhile, the infant mortality rate in Pasuruan Regency in 2015 was 7.73% of babies per 1,000 live births. And LBW is the second highest cause of death in Pasuruan Regency. The purpose of this study was to determine the relationship between maternal distance and the history of LBW with the incidence of low birth weight. The method used in this study is an analytical study with a cross-sectional approach, with a sample of 84 infants with a total sampling technique. Data on the relationship between maternal distance and the history of LBW were obtained from data collection sheets. Bivariate analysis was carried out with chi-square. Result: Pregnancy distance: Chi-square calculation result of Asimp value. Sig of 0.010 <0.05 and x² count 6.621 > x² 3.841 there is a relationship. LBW history: Chi-square calculation results in Asimp value. Sig of 0.000 <0.05 and x² count 29.403 > x² 3.841 then H0 is rejected. In conclusion, there is a relationship between maternal distance and a history of low birth weight with the incidence of low birth weight in Bangil Hospital, Pasuruan Regency.